Enhancing english speaking fluency for the first year students of faculty of english language in national economic university through role play activity = Nâng cao kỹ năng nói Tiếng Anh trôi chảy cho sinh viên năm nhất khoa Ngôn Ngữ Anh tại Trường Đại học Kinh tế Quốc dân thông qua hoạt động đóng vai - Bùi, Thi Mỹ Duyên (2020)
This is a micro-scale classroom action research conducted at the Faculty of English Language of one university in the capital of Vietnam. Based on the preliminary study, the researcher found that some first-year students have low ability of speaking fluency, which motivated the researcher to decide to implement role play technique in teaching speaking skill. The study aims at shedding the light on improving oral fluency of learners by acting in role plays as a good model for bringing real-life situations into the classroom. Both qualitative and quantitative methods that consist of some instruments such as speaking test, observation checklists, field notes along with questionnaires & interviews from the learners were used. The procedure of the research consists of four main stages: planning, implementation, observation and reflection. The findings of this research showed that the teacher saw a significant improvement in their students’ speaking fluency from one cycle to the following cycle and from both self-report of students. The role-playing procedures implemented by the researcher in this study consist of 7 major steps. Those are deciding on the teaching materials, organizing the group ofthe students, providing the situation and dialogue to be role played, teaching the dialogue for role plays, having the students practice the role plays, having the students modify the situation and dialogue, and having the students perform the dialogue in front of the class. The paper presents how role-playing technique improve the speaking ability of the students